Accountability in government and regulatory policies: Theory and evidence - Carmine Guerriero (Fondazione Eni Enrico Mattei (FEEM), 2008)
This paper analyzes the political economy of regulatory and judicial appointment rules. I study a model of price-setting by a political principal faced with a firm with unknown costs, and endowed with an information-gathering technology whose efficiency rises with the effort exerted by two accountable supervisors (a regulator and a judge). This set-up captures the institutions of several international markets. The model predicts that reforms toward election rather than appointment of regulators are more likely the less efficient is the information-gathering technology, the less stringent are the investment concerns of society, the stronger are regulators' revolving-door motivations, and the closer is political competition. These predictions are consistent with US electric power market data. Moreover, in accordance with the model, electricity rates are lower and respond less to shock in input costs in states that elect their regulators or their High Court judges.
Keywords: K23; L51; Q43; 330; Election; Agency; Judges; Regulation; Electricity